Seroprevalence of Chlamydia trachomatis infection among pregnant women and their outcome - Pipal, Vibha Rani; Pipal, Rajendra; Pipal, Dharmendra; Yadav, Seema; Kamal, Manoj; Singariya, Geeta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Genitourinary infections either sexually transmitted or by other means are a major concern among women, particularly young adults and teens. The objective was to find out seroprevalence of Chlamydia trachomatis infection in pregnant women and its effect on pregnancy outcome. Methods: the present study was carried out in the department of obstetrics and gynaecology, King George Medical University of Lucknow, Uttar Pradesh, India, over a period of September 2003 to July 2004. Total 120 pregnant women were included in the study, these pregnant women were selected according to their will in taking part in the study irrespective of age and parity. 2 ml of blood sample was collected and determination of antichlamydial IgM antibody was done by VIRCELL SL IgM ELISA Kit in microbiology department. Prevalence of chlamydia trachomatis in pregnant women were assessed and correlated with age group, parity, socioeconomic status, previous obstetric outcome, anaemia, PROM, mode of termination according to gestational age, perinatal outcome regards birthweight, and adverse neonatal outcome. Results: Out of 120 cases, total 70 (58.33%) were positive while the remaining 50 cases were negative. 80 cases were followed till delivery in which 66.25% were positive for antichlamydial IgM antibody. There was significant association of previous history of 2-3 abortion and preterm delivery with IgM positive cases. Low birth weight deliveries were 78% and very low birth weight was 100% in positive cases. Caesarean section at <37 weeks of gestation, IUGR and low APGAR score were significantly high in IgM positive group. 100% PROM cases were IgM positive. Conclusions: The prevalence of chlamydia trachomatis infection among pregnant women in our population is high and is strongly associated with premature rupture of membranes, IUGR, LBW, and low APGAR score deliveries.